Sleep duration, body composition and mortality: a prospective study of 156,565 Mexican adults - De Moraes-Ferrari, G (ELSEVIER, 2026)
Objectives: To investigate the joint association of sleep duration and body composition, assessed by body mass index (BMI) and waist circumference (WC), with all-cause, cardiovascular disease (CVD), and respiratory mortality among Mexican adults. Methods: This prospective cohort included 156,565 participants (median follow-up: 15.5 years), excluding those with pre-existing conditions and early deaths. Cox proportional hazards models estimated hazard ratios (HRs) for combinations of sleep duration (reference: 7-9 h/day for adults <65 years; 7-8 h/day for those >= 65 years; short sleep: <7 h/day; long sleep: >9 h/day for adults <65 years; >8 h/day for those >= 65 years) and body composition categories (normal weight, overweight, obesity; normal or high WC). Results: After full-adjustment, excess adiposity, particularly WC, emerged as the primary determinant of mortality risk, largely independent of sleep duration. CVD mortality risk was highest among individuals with high WC, particularly those with short sleep (HR: 7.28; 95 %CI: 2.22-23.79), with similarly elevated risks observed for high WC combined with reference or long sleep. Obesity was also independently associated with increased CVD mortality among individuals reporting reference sleep duration (HR: 3.11; 95 %CI: 1.28-7.55). For all-cause mortality, obesity increased risk across all sleep duration categories, while high WC was associated with elevated mortality regardless of sleep duration. No significant associations were observed for respiratory mortality after full adjustment. Conclusions: Sleep duration and body composition jointly influence mortality risk. Obesity and high WC substantially worsen these risks, underscoring the need for integrated strategies targeting both sleep and metabolic health.